Forest Fires and the Causes of Their Occurrence in Central Siberia - G. A. Ivanova; V. A. Ivanov; A. V. Musokhranova; A. A. Onuchin (Russian Academy of Sciences, Siberian Branch Publishing House, 2023)
On the territory of Central Siberia, hundreds of forest fires occur annually, spreading over vast areas. An analysis of the dynamics of forest fires showed that in recent decades the number of fires and the burned area have increased significantly. The average area of one fire has also increased, which indicates the insufficient effectiveness of the organization of forest fire protection. The maximum number of fires occurs in the Nizhneangarskiy taiga region, where pine forests predominate, in which cutting have been actively carried out since the middle of the last century. The largest burned area was registered in the Central Siberian plateau taiga region, where forests are inaccessible and a zone control by only remote-sensing instruments has been allocated. The largest number of fires from thunderstorms was also recorded in this forest region (93.1 %). The main number of large and catastrophic fires operated in the control zone. The meteorological factors influencing the occurrence of forest fires are analyzed and regression models of the dependence of the number of forest fires on temperature and precipitation for different forest regions are obtained. The main causes of fires are the emergence of a large number of fires sources due to the intensive economic development of forest areas and increased thunderstorm activity due to climate change. The use of a regression model of the relationship between the number of forest fires and the average air temperature and the amount of precipitation for the fire season allows to qualitatively estimate the system of protecting forests from forest fires. At the same time, in some forest regions, there is a decrease in the effectiveness of protecting forests from fires, the increase in the number of which is due to climate change.